THE DEATH PENALTY AS A MODEL TO PROVIDE A DETERRENT EFFECT AGAINST PERPETRATORS OF PREMEDITATED MURDER - Prayitno, Ahmad Hadi (UNISSULA, 2023)
The execution of the death penalty in cases of premeditated murder is, in fact, not easy. The old Criminal Code did not define the terms and conditions for premeditation elements. The purpose of this research is to analyze Death Penalty in Indonesia and The Urgency of Death Penalty in Creating A Deterrent Effect in Premeditated Murder. The method used in this legal research is normative juridical. Normative juridical research is research that is focused on examining the application of rules or norms in positive law. Indonesia is one of the countries that still maintain death penalty because death penalty is a criminal sanction that is still relevant in preventing and eradicating serious crimes. This can be seen in Constitutional Court Decision Number 2-3/PUU-V/2007. The provisions on death penalty for perpetrators of premeditated murder in the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code have made it difficult for death penalty to be imposed on perpetrators of premeditated murder.